THE RESEARCH ON WRITING CONDUCTED BY THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM - Abidin, Zainal; Supardi, Iwan; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research attempt to identify thesis writing: methods, research focus (teaching technique and media) and the educational level within the thesis. The appropriate method of this research is the descriptive method in which it provides information about conditions and events that occur in the present. The studentsâ€™ theses writing is selected based on ranging year from 2009 to 2013. The findings of this research are (1) Classroom Action research is the most preferable method selected by the students (2) 16 researches focused on teaching technique and eight others on teaching media, while three theses focused on both teaching technique and teaching media. (3) 17 researches conducted in the junior high, nine were in the senior high and two others were in the elementary school. This research may help the other students decide other potential methods, focuses and educational level as their main concerns for their future researches. Â  Keywords: identify, thesis, writing, research, methodologies. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi tesis dalam menulis: metode, fokus penelitian (teknik mengajar dan media) dan tingkat pendidikan di dalam tesis. Metode yang tepat dalam penelitian ini adalah metode deskriptif yang memberikan informasi tentang kondisi dan peristiwa yang terjadi di masa sekarang. Tesis dalam menulis dipilih di mulai dari tahun 2009 hingga 2013. Temuan penelitian ini adalah (1) Penelitian Tindakan Kelas adalah metode yang paling banyak dipilih oleh siswa (2) 16 penelitian difokuskan pada teknik pengajaran dan delapan penelitian pada media pembelajaran, sementara tiga tesis difokuskan pada teknik mengajar dan media penbelajaran. (3) 17 penelitian yang dilakukan di SMP, sembilan berada di SMA dan dua lainnya berada di sekolah dasar. Penelitian ini diharapkan dapat membantu siswa lain memutuskan metode-metode potensial lainnya, teknik dan media pembelajaran serta tingkat pendidikan karena untuk penelitian lebih lanjut. Kata Kunci: identifikasi, tesis, menulis, penelitian, metodologi.